The Influence of Content Marketing and Brand Awareness on Purchase Intention for Glad2Glow Products among the OhMyBeautyBank Community on X - Sabrina Kusuma Ningtias; Hendra Utama; Dian Septiana Sari (Universitas Dehasen Bengkulu, 2026)
The beauty industry has shown rapid growth in recent years and is expected to continue growing until 2030. This significant growth and potential has led to the emergence of many beauty brands. As a result, competition in the beauty market has become increasingly fierce, making a brand's ability to present interesting and relevant content and strengthen brand awareness an important factor in influencing consumer decisions. This study aims to analyze the influence of content marketing and brand awareness on the purchasing interest of Glad2Glow products among the OhMyBeautyBank community. This study uses a quantitative approach with an associative causal research type. Data collection techniques were carried out by distributing questionnaires to 100 respondents who are part of the OhMyBeautyBank community. The data was analyzed using multiple linear regression methods. The results show that content marketing partially has a positive and significant effect on purchase intention with a t-value of 4.144 and significance of 0.000. Brand awareness also partially has a positive and significant effect on purchase intention with a t-value of 7.247 and significance of 0.000. Content marketing and brand awareness simultaneously have a positive and significant effect on purchase intention with an F-value of 86.877 and a significance level of 0.000. The adjusted R Square value of 0.634 shows that content marketing and brand awareness can explain 63.4% of the purchase intention variable, while the rest is influenced by other variables outside the scope of this study. The findings in this study indicate that a good content marketing strategy and strong brand awareness can increase consumer purchase interest in Glad2Glow products.